Mosaics of faith : Floors of Pagans, Jews, Samaritans, Christians, and Muslims in the Holy Land - Talgam, Rina, (Treasures of the past (Jerusalem)., 2014)
"An analytical history of the Hellenistic, Roman, Byzantine, Umayyad, and Early Abbasid mosaics in the Holy Land from the second century B.C.E. to eighth century C.E."--Provided by publisher.